The Connection Between Baptism and the Reception of the Spirit in Becoming a Christian in Luke-Acts - Katja Hess (Religions, 2025)
The Traditio Apostolica presents, within the context of Christian baptism, first the water baptism accompanied by a profession of faith, followed by prayer with the laying on of hands. The purpose of this initiation process is the forgiveness of sins, which is more strongly implied in the water rite, and the gift of the Spirit, which is implied in the laying on of hands. This sequence of baptism and laying on of hands, in connection with faith and Spirit reception, is also evident in Acts 19:1–7. Apart from Acts 8:5–25, however, it is the only passage that links baptism with laying on of hands followed by Spirit reception. Moreover, it is the only instance of a rebaptism within the Lukan double work. The focus of this article is not primarily on the question of the historicity of this rite during the New Testament period but on a narratological-intratextual analysis of the relationship between baptism and Spirit reception, that is, to what extent the reader, against the background of the preceding narrative in Luke-Acts, is led to an understanding of this relationship and its significance for becoming a Christian. The article argues that faith plays a decisive role in the Christian initiation process.